Metal‐Halide Perovskite Crystallization Kinetics: A Review of Experimental and Theoretical Studies - Xie, Yue‐Min; Xue, Qifan; Yip, Hin‐Lap (Advanced energy materials, 2021)
Metal‐halide perovskites (MHPs) are regarded as ideal photovoltaic materials because of their variable crystal material composition and superb optoelectronic performance. However, this compositional variability results in a complicated crystallization process during MHP film fabrication, leading to reduced MHP film crystallinity and decreased performance of devices containing such films. The crystallization kinetics of MHPs have therefore been extensively explored in efforts to determine the effect of crystallization properties on MHP film properties and figure out the corresponding modulating strategies. Here, the first comprehensive review of reported studies on the crystallization properties of 3D MHPs is presented. The experimental and theoretical research on 3D MHP crystallization kinetics is systematically surveyed, and the methods that are used for modulating MHP crystallization are summarized, namely, solution engineering, compositional engineering, interfacial engineering, and additive passivation. Meanwhile, the prospects and current challenges in revealing perovskite crystallization kinetics are suggested. The vast literature on experimental and theoretical research on the nucleation and growth of metal‐halide perovskite films, as well as the relationships between film properties and crystallization modulating methods including solution engineering, composition engineering, interface engineering, and additive passivation are systematically reviewed. This work consolidates the research on metal‐halide perovskite crystallization kinetics, and highlights new and promising areas of study.